(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: Toxic shock syndrome (TSS) is a severe multisystemic condition caused by Staphylococcus aureus or Streptococcus pyogenes, and initial management of skin lesions is essential for infection control. This article aimed to describe skin care for TSS. Case report: We report a man with a hip abscess who developed fever and hypotension and was subsequently transferred to an intensive care unit (ICU). He was diagnosed with septic shock, probably of hip origin, and was immediately treated surgically for local infection control. He presented with renal failure besides multiple organ dysfunction (hepatic and cardiac), hemodynamic instability, and disseminated skin lesions. With the isolation of Staphylococcus aureus, clindamycin was initiated, and the diagnosis was TSS due to epidermolytic lesions since the onset of the condition. Cutaneous recovery measures were initiated with silver sulfadiazine, followed by silver hydrofiber with skin recovery in 8 days. After 10 days of skin recovery, the patient was discharged from the ICU to the ward with maintenance of the proposed treatment. Conclusion: In this case, the use of hydrofiber showed satisfactory performance; however, robust studies are needed to confirm such efficacy.